If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + -6 + -3y + 3 = 0 Reorder the terms: -6 + 3 + 8y + -3y = 0 Combine like terms: -6 + 3 = -3 -3 + 8y + -3y = 0 Combine like terms: 8y + -3y = 5y -3 + 5y = 0 Solving -3 + 5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 5y = 0 + 3 5y = 0 + 3 Combine like terms: 0 + 3 = 3 5y = 3 Divide each side by '5'. y = 0.6 Simplifying y = 0.6
| 4k-5(k-8)=2(k+2) | | 5x+10(52-x)=450 | | 63=5v-12 | | 3(x+1)-2(3x-7)=14 | | 25x^2+x-3=0 | | x^2-6x=-2x+60 | | x-2=144 | | 5(2x-3)=14 | | y-18+5x=0 | | 12-3x=22+5x | | 108=72-180 | | 2m-3m-8n+n= | | 5(y+7)+-2(3+y)= | | 13y-9y-10=53.48 | | (3x+8)+(3x+7)+(3x)=(3x)+(3x)+(4x+5) | | 5x-3+2x+1=8+3x+2 | | 27=3z-5z+9+4z | | -7(3y+2)=8(3y-2) | | 6x+3[2y-x]= | | -2x-39=59-9x | | -9.39+-3.4d=-1.1d+11.08 | | b+3-6b=-3+b | | 2x+3x+-5=90 | | 30-6x=16+8x | | 33-7p=8(1-4p) | | 5x-27=3x+11 | | y=(3x+10)+(-5x+200) | | -2(1-3u)-6=-2(4u+4) | | -6x+3+-9x= | | 6-8x=5x-10x+12 | | 5n+9=2n-3 | | -5=5+y |